Influência de fatores ambientais na incidência do vírus da infecção hipodermal e necrose hematopoiética (IHHNV) no camarão Litopenaeus vannamei cultivado em fazendas do Estado do Rio Grande do Norte (RN) - Silva, Cimária Porfírio Rodrigues de Oliveira da (2008)
The shrimp farming industry is the most profitable area of the aquaculture at Rio Grande do Norte (RN) state, which is one of the largest producers in Brazil. However the infections that affect the shrimp cause major economic losses. The infection is a result of the interaction between the shrimp, the environment and pathogen. The change of these factors may lead to a condition of stress and susceptibility to opportunistic infections. One of these infections caused by Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV) is widely distributed in several countries and affects a wide range of hosts. To optimize conditions for production of Litopenaeus vannamei shrimp, the more species cultivated in Brazil, it is necessary to understand the effects of environmental factors in the susceptibility of this species to infections. The aim of this study was to determine the IHHNV prevalence and to investigate the influence of environmental factors as salinity, temperature, stocking density, dissolved oxygen and rainfall in the IHHNV incidence in L. vannamei grown in farms, in the RN state. To determine the IHHNV prevalence were used 1089 samples of L. vannamei collected in seven farms. To perform the study about the influence of environmental factors, 525 samples of L. vannamei shrimp were collected in eight farms located in regions of low (0-1 ), medium (21-30 ) and high (38-57 ) salinity, using extensive (≤15 shrimp/m2 ), semi-intensive (18-33 shrimp/m2) or intensive (>36 shrimp/m2) stocking density systems. The IHHNV infection was determined in pleopod and hemolymph using the polymerase chain reaction (PCR). The environmental factors were recorded during the collection of animals, using a refractometer to measure the salinity and a multi-parameter meter to measure the temperature and concentration of dissolved oxygen in the water. The IHHNV prevalence in RN was 43% (468 infected shrimp out of 1089), varying on different farms. On the seven farms studied, IHHNV prevalence ranged from 18.6% to 54.8%. The infection rates in the shrimp cultured in low, medium and high salinity were respectively 43.10% (125/290), 31.2% (15/48) and 24.6% (46/187) and was significantly higher in shrimp grown in low salinity (P<0.001). The infection rates in ponds of extensive, semi-intensive and intensive systems were respectively, 28.7%, 28.28% and 47.84%, and was significantly higher in high stocking densities (P<0.001). This study indicated a high IHHNV prevalence and a significant effect of salinity and stocking density, but not of the temperature, rainfall and dissolved oxygen on the IHHNV infection rate in the L. vannamei shrimp cultured in the northeastern Brazil